2005
DOI: 10.1007/s00436-005-1298-6
|View full text |Cite
|
Sign up to set email alerts
|

Repellent efficiency of BayRepel against Culicoides impunctatus (Diptera: Ceratopogonidae)

Abstract: A new insect repellent, BayRepel, containing the active ingredient KBR 3023, was examined for repellent efficiency against the biting midge Culicoides impunctatus Goetghebuer. Assessments were made using landing rates on the forearms of five human subjects with two treatment concentrations of BayRepel and also an alternative repellent, Mosi-guard. BayRepel was found to significantly reduce landing rates for over 8 h, but with a significant reduction in efficiency at 2-4 h post-application. Increasing the dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Insecticide use in these areas is often forbidden due to environmental regulatory issues. Repellents only provide minimal and temporary relief and are not considered a long-term solution (Carpenter et al 2005, Schreck and Kline 1981, Trigg 1996. Apart from altering one's life-style when midges are presented by staying indoors, repellents are presently the only means of self-protection.…”
Section: Control and Field Based Experimentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Insecticide use in these areas is often forbidden due to environmental regulatory issues. Repellents only provide minimal and temporary relief and are not considered a long-term solution (Carpenter et al 2005, Schreck and Kline 1981, Trigg 1996. Apart from altering one's life-style when midges are presented by staying indoors, repellents are presently the only means of self-protection.…”
Section: Control and Field Based Experimentationmentioning
confidence: 99%
“…Several chemicals related to DEET have been tested against midges and shown to be similar or more effective than DEET with respect to length of and degree of protection. One such compound, Bayrepel ® , tested by Carpenter et al (2005) on the Scottish biting midge proved to be effective for up to 8 hours post application. Plant essential oils such as citronella and eucalyptus, PMD (p-menthane-3,8-diol), isolated from lemon eucalyptus oil of Eucalyptus citriodora Hook.…”
Section: Olfaction In Vector-host Interactions 235 10 Understanding mentioning
confidence: 99%
“…Picaridin [2-(2-hydroxyethyl)-1-piperidinecarboxylic acid 1-methylpropyl ester] is a new insect repellent for human use (Wahle et al, 1999;WHO, 2000;Scheinfeld, 2004;Carpenter et al, 2005), with initial registration in the U.S. in 2001 (USEPA, 2005). It has been shown to be effective against mosquitoes and a wide range of hematophagous arthropods (Frances et al, 2004;Scheinfeld, 2004;Carpenter et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to be effective against mosquitoes and a wide range of hematophagous arthropods (Frances et al, 2004;Scheinfeld, 2004;Carpenter et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Europe showed that compounds such as p-menthane-3,8-diol (PMD), N,N-diethyl-m-toluamide and KBR3023 (Picaradin) will reduce the Culicoides biting rate on humans (Carpenter et al 2005;Trigg 1996). In South Africa 15% DEET (Page et al 2009) and a 15% (w/w) mixture of octanoic, nonanoic and decanoic acids (C9810) in light mineral oil ) was shown to have a significant repellent effect against Culicoides species when applied to polyester mesh.…”
Section: Introductionmentioning
confidence: 99%